2023
DOI: 10.1177/08445621231159164
|View full text |Cite
|
Sign up to set email alerts
|

The Canadian Landscape of Genetics and Genomics in Nursing: A Policy Document Analysis

Abstract: Background Genetics and genomics (GG) are transforming approaches to healthcare in Canada and around the globe. Canadian nurses must be prepared to integrate GG in their practice, but modest research in this area suggests that Canadian nurses have limited GG competency. Countries that have integrated GG across nursing provided guidance to nurses about the practice implications of GG through regional nursing policy documents. These documents propelled action to integrate GG across nursing. Little is known about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Third, themes were organized according to the continuum of care, from primary prevention to rehabilitation. Last, as a validation step, and a safeguard against potential bias, we juxtaposed our findings against studies focusing on genomic disparities that were identified by a systematic scoping review and a health policy analysis that examined the current state of genomics in nursing (Puddester et al, 2023;Thomas et al, 2023). medical history and a three-generation family history to identify at-risk individuals and refer them to specialized services.…”
Section: Methodsmentioning
confidence: 99%
“…Third, themes were organized according to the continuum of care, from primary prevention to rehabilitation. Last, as a validation step, and a safeguard against potential bias, we juxtaposed our findings against studies focusing on genomic disparities that were identified by a systematic scoping review and a health policy analysis that examined the current state of genomics in nursing (Puddester et al, 2023;Thomas et al, 2023). medical history and a three-generation family history to identify at-risk individuals and refer them to specialized services.…”
Section: Methodsmentioning
confidence: 99%